La sobreprotección infantil - Cando Yaguar, Myrian Elizabeth (2017)
The research project on child overprotection and its impact on the language development of children in the third grade students is carried out with the purpose of knowing the relation between the family environments of excessive protection towards children and the Deficient language development that children present in the third grade, considering the current overprotection in an existing problem and with a high incidence rate in educational institutions. For research development it is proposed the use of a research methodology of mixed type framed in the bibliographical-documentary and field research that allow quantitative and qualitative analysis to understand the effects caused by overprotective parents in the language domain of children . The research project seeks to benefit 137 people among children, teachers, parents and authorities of the institution in order to raise awareness about this problem. It is important that the educational community as a whole analyze the needs of children as well as the autonomy to achieve a better physical, psychological and social development of children in the third grade of education basic. Framed in the constructivist approach to learning, experience becomes a key element for the cognitive development of children, because it allows them to elaborate their own knowledge based on the interaction with the subjects and objects that are in their environment.